Prevalence of tuberculosis among health care workers in tuberculosis specialized hospitals in China. Issue 3 (20th May 2017) - Du, Jian; Pang, Yu; Ma, Yan; Mi, Fengling; Liu, Yuhong; Li, Liang
Abstract : Objectives: Tuberculosis (TB) specialized hospitals are playing an increasingly important role in the diagnosis and treatment of patients with TB in China. This study aimed to investigate the prevalence of TB among health care workers (HCWs) in TB specialized hospitals in China. Methods: We conducted a crosssectional survey to collect longitudinal information on the number of HCWs and patients with TB from HCWs among 203 TB hospitals in China. Results: Overall, these 186 TB cases accounted for the incidence of 985 per 100, 000 population. The prevalence ratios among medical professionals (PR = 2.40) and laboratory technicians (PR = 2.17) were significantly higher than other hospital staff (PR = 1.04). In addition, general hospitals with TB clinics had the highest prevalence ratio of TB (PR = 5.15), while designated TB hospitals had the lowest prevalence ratio (PR = 1.48). Conclusion: Our findings demonstrated that HCWs are suffering from an increased risk of infection with TB in China, and medical professionals (physicians and nurses) and general hospitals with TB clinics have the highest prevalence ratio of TB.